The Influence of Organizational Culture on Employee Performance with Work Motivation as a Mediation Variable in UPT. Regional Revenue Agency of North Kalimantan Province - Syahran; Alimin, Muhammad Ichsan; Basran, Zakaria; Marsha, Deni; Hasyim, Budi; Ardiyansyah, Riyans (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
This study aims to analyze the influence of organizational culture on employee performance, with work motivation as a mediating variable in UPT. Regional Revenue Agency of North Kalimantan Province. This study uses a quantitative approach with a survey method through a questionnaire distributed to 144 ASN employees as a sample. Data analysis was carried out using the Partial Least Squares (PLS) method through SmartPLS 3.0 software. The results of the study show that organizational culture has a positive and significant effect on employee performance, both directly and indirectly through work motivation. In addition, organizational culture also has a significant effect on work motivation, and work motivation significantly affects employee performance. These findings confirm the importance of the role of organizational culture and work motivation in improving employee performance. Therefore, organizations need to build a work culture that supports and pays attention to the motivational aspects of employees to create optimal performance